Influence of toll-like receptors - 4 on the pathogenesis of the development of anemia of inflammation in young children with acute bacterial respiratory diseases - Pogribna, A. O.; Погрібна, Анастасія Олександрівна (Запорізький державний медичний університет, 2021)
Aim. To determined the pathogenetic role of Toll-like receptors-4 (TLRs-4) in the development of anemia of inflammation (AI).
Keywords: тези